QT prolongation and excessive variability predicts new-onset atrial fibrillation in the health screening data of Japanese adults - Yuichi Ninomiya; Kei Enokizono; Shin Kawasoe; Takuro Kubozono; Hiroyuki Kamada; Yasuhisa Iriki; Yoshiyuki Ikeda; Hironori Miyahara; Koichi Tokushige; Mitsuru Ohishi (PLoS ONE, 2025)
Background A prolonged QT interval (QTc) is associated with the development of atrial fibrillation. However, reports linking QTc variability and atrial fibrillation are limited. Purpose To investigate the relationship linking prolongation and variability of QTc with new-onset atrial fibrillation in Japanese adults. Methods This retrospective study analyzed the annual health screening data of 103,304 adults (50,438 males; mean age, 54 years) who did not exhibit atrial fibrillation at baseline between April 2005 and October 2018. The majority of the study population underwent annual health examinations according to Japan’s health welfare policy. We calculated QTc times using the Bazett formula (QTc = QT/√RR). QTc variability is indicated by the gap between the maximum and minimum QTc values. Atrial fibrillation was diagnosed by 12-lead surface electrocardiography. The association between QT prolongation and variability in new-onset atrial fibrillation was ascertained by logistic regression analysis. The strength of the association was further analyzed using multivariable analyses adjusted for sex, age, dyslipidemia, diabetes, hypertension, obesity, estimated glomerular filtration rate, and alcohol consumption. Results During the follow-up (median six years), we recorded 341 (0.3%) new atrial fibrillation cases. Univariable analysis showed a significant association between QTc prolongation and variability with new-onset atrial fibrillation (odds ratio [OR] per 10 ms, 1.08 and 1.15; 95% confidence interval [CI], 1.03–1.13 and 1.07–1.23, respectively; P < 0.001). Multivariable analysis suggested increased risk of new-onset atrial fibrillation with QTc prolongation and QT variability (OR per 10 ms, 1.09 and 1.16; 95% CI, 1.04–1.14 and 1.09–1.24, respectively; P < 0.001). Conclusion In the general Japanese population, QTc prolongation and large QT variability are risk factors for new-onset atrial fibrillation. QT prolongation and large QT variability during sinus rhythm may be good markers for predicting not only ventricular but also atrial arrhythmias such as atrial fibrillation.